Descemet stripping endothelial keratoplasty: One-year follow-up - Nikolić Ljubiša; Jovanović Vesna (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction. Sutureless transplantation of endothelium on a thin stromal carrier was introduced under the name of Descemet stripping endothelial keratoplasty (DSEK) in 2004. It has become the treatment of choice of corneal oedema due to endothelial dysfunction. Objective. To investigate posterior lamellar graft attachment, central corneal thickness (CCT), astigmatism, and best corrected visual acuity (BCVA) during one-year follow-up. Methods. Surgery was performed on one eye of 11 patients with pseudophakic bullous keratopathy and Fuchs’ dystrophy. The graft thick 150-200 μm and 8.0 mm in diameter was detached manually. The carrier of the recipient cornea was created by DSEK. The graft was folded in half, introduced into the anterior orbital chamber through a 5.0 mm cut on the limbus and attached by air bubble along the internal side of the recipient cornea. CCT and astigmatism were evaluated by corneal topography, and graft attachment by biomicroscopy. Results. One year after surgery, all grafts remained attached. Primary graft failure occurred in three eyes, probably due to the crushing effect of the forceps. BCVA was 20/30 (2 eyes), and 20/40 (6 eyes), CCT 643-728 μm, and astigmatism 1.1 D to 2.9 D. The peak values were reached three months after surgery, and did not change much afterwards. Conclusion. This is the first report on the long-term results of DSEK in our literature. The results are similar to those obtained by more experienced DSEK surgeons, and suggest that this procedure is safe and successful.